Trends in Research on Art Therapy Indexed in the Web of Science: A Bibliometric Analysis - Rodriguez Novo, Natalia; Novo Muñoz, Maria Mercedes; Cuellar-Pompa, Leticia; Rodriguez Gomez, Jose Angel (Frontiers in Psychology, 2021)
Despite the increase in international research in Art therapy, few studies have been developed with a bibliometric approach which describe the situation regarding this area of knowledge. Thus, the aim of this study is to describe and contextualize international scientific production in the visual arts modality in the context of artistic therapies, to offer a broader and more in-depth vision of the structure of this area of knowledge through of a bibliometric analysis of the publications indexed in the main collection of the Web of Science. This is a retrospective, exploratory and descriptive, cross-sectional study to analyze the bibliographic data retrieved from the databases of the main WOS collection. The analysis parameters included the data corresponding to the production according to type of document, country, journal and institution. In addition, the main lines of research were located and classified and the subject matter of the most cited articles in each of them was summarized. A total of 563 works were published, in 250 journals, in the 63 years between 1958, when the first document was published, and April 2021. The annual growth rate was 7.3% with a mean average of 8.7 publications per year, and 83.13% of the published works were articles. A total of 1,269 authors from 56 countries were counted. The mean number of citations per document was 5.6 and the mean number of citations per document and year was 0.6. The main research domains were psychology and/or rehabilitation. In general, a high degree of variability was observed in the study topics and numerous theoretical and methodological articles. The most used visual arts modalities were in the main drawing, painting and photography. This work did not find previous existence of any bibliometric analysis on the international scientific production in art therapy. In general terms, there has been a substantial growth in the number of publications on the subject over the last decade. However, this research area does not appear to have peaked, but, on the contrary, is still growing and progressing despite its long history in clinical practice.